'Brown Morning:' classed interpretations of anti-racist text. Issue 1 (2nd January 2018) - Amir, Dana; Shoshana, Avihu
ABSTRACT: This article examines the interpretations of high school students from different socioeconomic locations (in terms of socioeconomic class and ethnicity) with regard to the text Brown Morning, used as a didactic tool for antiracism education within the framework of Civics courses. The research findings uncover differences in the students' interpretations of the text. An in-depth understanding of these differences will be attained through clinical analyses based on the distinctions between metaphor and metonymy made by linguist Roman Jakobson. Among students from low socioeconomic locations, interpretations related to racism were dominated by metonymic characteristics, while that of students from higher socioeconomic locations were predominantly metaphoric . Study findings do not only show the different interpretations among the students, but also the various ways in which metaphorical and metonymic language affect teachers. These analyses will focus on the reasons for these differences and their implications regarding the links between social locations, language, and education.